2017
DOI: 10.1002/jcla.22190
|View full text |Cite
|
Sign up to set email alerts
|

A genetic variant in CDKN2A/B gene is associated with the increased risk of breast cancer

Abstract: Background Breast cancer is among the leading cause of cancer‐related‐deaths in women, supporting the need for the identification of novel prognostic and predictive biomarkers. Recent studies have identified common genetic variants in a region on chromosome 9p21 associated with an increased risk of developing different cancers. Here, we explored the association of a genetic variant in CDKN2A/B, rs10811661, for the first time in 564 subjects with/without breast cancer. Method Genotyping was performed using TaqM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 19 publications
2
18
1
Order By: Relevance
“…15,16,18 According to the obtained results, the allele C was the risk allele and the subjects who expressed this genotype were more susceptible to breast cancer. In contrast, our data was not confirmed by Shahidsales et al 57 They showed that the TT allele had the risk allele associated with breast cancer (OR, 4.9; 95% CI, 1.9 to 12; P < 0.001). Furthermore, Driver et al evaluated the 13-cell cycle involved genes with the risk of breast cancer.…”
Section: Discussioncontrasting
confidence: 99%
“…15,16,18 According to the obtained results, the allele C was the risk allele and the subjects who expressed this genotype were more susceptible to breast cancer. In contrast, our data was not confirmed by Shahidsales et al 57 They showed that the TT allele had the risk allele associated with breast cancer (OR, 4.9; 95% CI, 1.9 to 12; P < 0.001). Furthermore, Driver et al evaluated the 13-cell cycle involved genes with the risk of breast cancer.…”
Section: Discussioncontrasting
confidence: 99%
“…We studied the value of the CDKN2A/B‐rs1333049 and its expression with a high risk of breast cancer for the first time. Our study reported a higher susceptibility in holders GC/CC genotypes to breast cancer, which is in line with our previous studies (Ghobadi et al, 2017; ShahidSales et al, ), and other studies in pancreas and breast carcinomas and also multiple melanomas (Borg et al, ; Burdon et al, ; Dębniak et al, ; Sherborne et al, ; Yang et al, ). Li et al () analyzed 9p21 SNPs in a large scale study, including studies of breast cancer, renal cell carcinoma, ESCC, and pancreatic cancer.…”
Section: Discussionsupporting
confidence: 92%
“…Previously, we showed the association of CDKN2A/B rs10811661 in 564 subjects suffering from breast cancer. This data showed that those with the TT genotype for CDKN2A/B polymorphism had a growing risk of susceptibility to BR (ShahidSales et al, ). In another study of our group, the associations of two SNPs; rs1333049 and rs10811661 located in CDKN2A/B loci were assessed with clinical features of individuals with esophageal squamous cell carcinoma.…”
Section: Introductionmentioning
confidence: 97%
“…Case-control studies have suggested several genetic markers that are associated with breast cancer risk within various populations (Ghoussaini et al, 2012). Previous studies have suggested that the 9p21 locus gene variants (rs1011970 and rs3088440) are associated with an increased risk of breast cancer (Royds et al, 2016;ShahidSales et al, 2017). The genes at the 9p21 locus encode several important proteins.…”
Section: Introductionmentioning
confidence: 99%